Predicting the cost of malaria elimination in the Asia-Pacific - Shretta, R; Silal, S; White, LJ; Maude, RJ (F1000Research, 2019)
Over the past decade, the countries of the Asia-Pacific region have made significant progress towards the goal of malaria elimination by the year 2030. It is widely accepted that for the region to meet this goal, an intensification of efforts supported by sustained funding is required. However, robust estimates are needed for the optimal coverage and components of malaria elimination packages and the resources required to implement them. In this collection, a multispecies mathematical and economic modelling approach supported by the estimated burden of disease is used to make preliminary estimates for the cost of elimination and develop an evidence-based investment case for the region.